Cardiovascular Risk Assessment in Type 2 Diabetic Patients at Universitas Sumatera Utara Hospital - Faza Ulya Putri; Naomi Niari Dalimunthe; Ginting, Andi Raga; Isti Ilmiati Fujiati (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background. Diabetes is a major health problem worldwide including in Indonesia. There is a close relationship between diabetes and cardiovascular disease, with cardiovascular events being the most prevalent cause of morbidity and mortality in diabetic patients. Therefore, it is important to assess cardiovascular risk in patients with diabetes in order to conduct appropriate preventive strategies. Various methods have been developed to assess the degree of cardiovascular risk, one of which is the Jakarta Cardiovascular Score, a scoring method that has been adapted for the Indonesian community. This study aims to describe the profile of cardiovascular risk in diabetes patients at Universitas Sumatera Utara Hospital. Methods. A descriptive, cross-sectional study was conducted in the internal medicine outpatient clinic at Universitas Sumatera Utara Hospital. All subjects were diabetic patients who had not developed any cardiovascular complications. The risk of cardiovascular disorders was assessed using the Jakarta Cardiovascular Score. Data were collected through medical records, interviews, and physical examinations. Results. There were 64 subjects in this study. The majority of subjects (81.3%) were classified as high risk for cardiovascular disease. Conclusion. Most patients with diabetes have a high degree of risk of cardiovascular disease.